Groupes d’entreprises dans l’enseignement de base public brésilien: Limites à mise en oeuvre du droit à l’éducation - Adrião, Theresa Maria De Freitas; Garcia, Teise de Oliveira Guaranha; Borghi, Raquel Fontes [UNESP]; Bertagna, Regiane Helena [UNESP]; Paiva, Gustavo Bottura; Ximenes, Salomão Barros (FapUNIFESP (SciELO), 2016)
This paper analyzes, based on primary sources, mainly official and institutional documents, and on interviews with municipal managers, the performance of five business groups in municipal basic education systems. It is aimed to identify the outcomes of the adoption of private education systems by Brazilian municipalities for the composition of earmarked revenues spending for education and for the right to education. The research confirms previous studies that indicates the shift of public funds to the private sector, including transnational corporations.
Grupos empresariais na educação básica pública Brasileira: LIMITES À Efetivação do direito à educação
Corporate groups in the brazilian public basic education: Limits on the realization of the right to education
Keywords: Private education systems; Privatization; Right to education